2007 IEEE 10th International Conference on Rehabilitation Robotics 2007
DOI: 10.1109/icorr.2007.4428407
|View full text |Cite
|
Sign up to set email alerts
|

Walking Phase Recognition for People with Lower Limb Disability

Abstract: This paper presents a total solution on EMG signal-based walking phase recognition for people with lower limb disability. Various environmental factors such as sensed location, walking speed, and ground inclination are taken into consideration in all the phases of signal sensing, feature extraction, feature selection, and classification. Based on analysis on fourteen well-known feature extraction methods in varying environmental situation, this paper proposes a methodology for selecting a good feature set, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Many researchers have adopted surface electromyogram (sEMG) signals to recognize gait for the control of lower-limb exoskeletons (or prostheses) [7]. Due to their capability for of revealing the inner workings of the human motor nerve system, sEMG signals can directly reflect the subject's intended activity, and the motor function instruction information of the neuromuscular system [8]. In addition to the convenience and non-invasive nature of the signal acquisition, sEMG signals are also widely used as a neural control source for human-machine interaction, such as the control of lower-limb exoskeletons (or prostheses).…”
Section: Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have adopted surface electromyogram (sEMG) signals to recognize gait for the control of lower-limb exoskeletons (or prostheses) [7]. Due to their capability for of revealing the inner workings of the human motor nerve system, sEMG signals can directly reflect the subject's intended activity, and the motor function instruction information of the neuromuscular system [8]. In addition to the convenience and non-invasive nature of the signal acquisition, sEMG signals are also widely used as a neural control source for human-machine interaction, such as the control of lower-limb exoskeletons (or prostheses).…”
Section: Instructionmentioning
confidence: 99%
“…There are several practical limitations for sEMGs for use in gait recognition for the control of exoskeletons and prostheses. Lee et al [8] demonstrated that performance in gait recognition is not guaranteed as a result of the influence of the variable environmental factors. The most common variable factors include different lower-limb positions [11,12], sEMG signal instability [13], displacement of the electrode [14], and so on; moreover, load variation is a problem that cannot be ignored.…”
Section: Instructionmentioning
confidence: 99%